Educación ambiental virtual para el mejoramiento en el manejo de residuos sólidos en la Unidad Educativa Francisco González Álava, sitio Arrastradero-Calceta - Gaón Rojas, Gema Gabriela (2022)
The objective of this research was to implement a virtual environmental education training plan for solid waste management in the Francisco González Álava Educational Unit. A diagnosis was made through an initial evaluation of 36 students from fifth to seventh year of basic education, 63% obtained a sufficient level of knowledge on the subject; 23 students of general basic education [EGB], 56% obtained a sufficient level of knowledge; 44 students of high school, 43% obtained a sufficient level of knowledge; and 16 teachers, authorities, 43% obtained a sufficient level of knowledge on solid waste management. With the information obtained, an environmental education training plan on solid waste management was implemented, which was divided into two plans; one for students and the other for teachers and authorities, where those involved participated in the training with an 87.5% satisfaction rate. Then a final evaluation was assigned, where 51 students from fifth to seventh year of basic education, 45.1% obtained an excellent level of knowledge; 36 of General Basic Education [EGB], 47.22% have an excellent level of knowledge; 32 of high school, 59.13% have an excellent level of knowledge and 81.25% of teachers and authorities reached an excellent level of knowledge on solid waste management; a virtual practical guide was designed to strengthen the knowledge of solid waste management in the institution